2015
DOI: 10.1097/yic.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of the My Medicines and Me Questionnaire for assessment of the self-reported side effects of psychotropic medication

Abstract: We aimed to construct and assess the psychometric properties of the My Medicines and Me Questionnaire (M3Q), a self-report side-effect questionnaire for mental health patients. Thirty individuals taking a psychotropic medication completed the M3Q side-effect checklist along with the Liverpool University Neuroleptic Side Effect Rating Scale. Thirty healthy comparison individuals also completed the M3Q checklist. Data were analyzed using factorial analysis. Psychometric evaluations including validity and reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This finding further highlights the need for screening for, and managing, MRPs in this population. The inclusion of the M3Q tool [ 34 ], which is readily available for pharmacists to access [ 46 ], in the Initial Health Review may have facilitated further discussion with consumer participants about medication related adverse effects compared to other types of MRPs. Regardless, the identification of numerous MRPs, irrespective of type, across both populations indicates the importance of timely access to services which are tailored to the needs of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding further highlights the need for screening for, and managing, MRPs in this population. The inclusion of the M3Q tool [ 34 ], which is readily available for pharmacists to access [ 46 ], in the Initial Health Review may have facilitated further discussion with consumer participants about medication related adverse effects compared to other types of MRPs. Regardless, the identification of numerous MRPs, irrespective of type, across both populations indicates the importance of timely access to services which are tailored to the needs of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the intervention was intended to be holistic, with medication review forming a component of the intervention, emphasis was placed on physical health and wellbeing. Further instruments were made available to pharmacists to help with issue identification, including the My Medicines and Me Questionnaire (M3Q) which can assist in the detection of side-effects from psychotropic medication use [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, antipsychotic treatment is associated with side effects, including weight gain, sexual dysfunction, extrapyramidal symptoms, and sedation (Ames et al, 2016; Papola et al, 2019; Solmi et al, 2017; van Strien et al, 2015). Studies have shown the presence of side effects is associated with physical and psychological morbidity, reduced quality of life and high rates of discontinuation of pharmacological treatment (Ashoorian et al, 2015; Correll et al, 2017; Firth et al, 2019; Kane et al, 2013; Vancampfort et al, 2016; Vancampfort et al, 2015; Wykes et al, 2017; Young et al, 2015). Furthermore, differences in side effect profiles between antipsychotics are more marked than the relatively smaller differences in efficacy (Huhn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Formal psychometric testing has been carried out on the closed questions resulting in 32 items in the checklist component [Ashoorian et al 2015]. The final version of the M3Q is given in Appendix 1.…”
Section: Discussionmentioning
confidence: 99%